Obliteration of Dentinal Tubules by Desensitizing Agents Based on Silver Fluoride/Potassium Iodide or Pre-Reacted Glass Particles: An in Vitro Study - Fernanda Novais Arantes Maciel de Castro; Diandra Costa Arantes; Wagner Nunes Rodrigues; Allyson Nogueira Moreira; Cláudia Silami Magalhães (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the efficacy of desensitizing agents for the obliteration of dentinal tubules subjected or not to a simulated oral environment. Material and Methods: Dentinal discs (n=8) treated with Riva-Star (RS) or PRG-Barrier-Coat (PRG) were submitted (cycled) or not submitted (control) to erosive-abrasive-thermal cycles and evaluated using scanning electron microscopy/energy dispersive spectroscopic analysis. The variables analyzed were tubule obliteration and dentin surface chemical composition. Data were analyzed by non-parametric tests (p<0.05). Results: The cycled and control groups did not differ significantly for the responses in each material. The PRG control and cycled groups had fewer visible tubules and a higher proportion of totally obliterated tubules than the RS groups. The percentages of silver coverage were higher in the RS-control than in the RS-cycled. There was a significant inverse correlation between the presence of silver and non-obliterated tubules (R=-0.791; p<0.001). The percentages of carbon, aluminum, strontium, and potassium were significantly higher in the PRG-control and PRG-cycled compared to the RS control. The percentages of calcium, phosphorus, and silver were significantly higher in the RS compared to the PRG groups. PRG-control showed a higher percentage of boron than RS-control. Conclusion: PRG promoted greater tubule obliteration than SR. Simulated stress did not affect the obliterating effect of each agent. Greater silver coverage corresponded to a lower proportion of non-obliterated tubules in RS. Carbon, aluminum, strontium, boron, and potassium predominated in the dentin surface treated with PRG, while calcium, phosphorus, and silver prevailed in RS groups.